ANALYSIS OF OIL/WATER EMULSION IN THE PRODUCTION AND DUMPING ZONES OF OIL WELL BY CFD TECHNIQUE - ABDUL JAMIL, IYLIA ELENA (2017)
Oil/water mixture production in oil production wells is a common phenomenon. It is of high interest to the oil industry to process the oil/water separation in the downhole, by hydrocyclone technology. Oil and water separation methods have focused on the separation process and the hydro fluid behavior within the separator body while there is a lack of studies and simulations on the wellbore flow behavior before and after the separation. Accordingly, this work is directed to investigate the mixture flow structure in the production and in the water dumping zones. A computational modelling and numerical simulation using CFD technique is described in this thesis for the oil and water flow inside the wellbore before and after separation by counter current hydrocyclone. The simulation was conducted for a two-phase flow using ANSYS-Fluent 15 software and it was attempted to visualize the volume fraction and density profiles in a natural downhole environment. The well geometries and the oil/water production candidates at the downhole have been adopted from a real well in an offshore field in Malaysia. Four cases of oil-to-water mixing ratios have been considered, as 90:10, 70:30, 50:50 and 30:70, and the separator efficiency was assumed to be 90%. The results illustrate the great complexity of oil in water flows, reflecting the many competing processes, like turbulence, gravitational separation, droplet interaction and the shear between the two liquids and with the solid surfaces, which are occurring in the annulus. In the zone before the separator, the production zone, distribution of the oil volume fraction depends highly on the mean oil volume fraction and the vertical length of the zone without perforations. The contour results from the simulation showed that the phases mix and achieve uniform distribution as the flow proceeds down the channel. The present simulation could be used to better predict the behavior of oil/water mixture flow inside the wellbores with the presence of a hydrocyclone, and also can be modified to simulate the wells with production at lower zone and dumping at upper zone.